2021
DOI: 10.1111/jgs.16994
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregiver Assessment in Primary Care: How to Strengthen the HealthCare Triad?

Abstract: This editorial comments on the article by Riffin et al. in this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In fact, some teams were developing procedures within their primary care networks to support the family caregivers who were registered patients. These results reflect the increasing interest in healthcare providers' role in supporting family caregivers [36][37][38].…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…In fact, some teams were developing procedures within their primary care networks to support the family caregivers who were registered patients. These results reflect the increasing interest in healthcare providers' role in supporting family caregivers [36][37][38].…”
Section: Discussionmentioning
confidence: 56%
“…Interpretive description was designed to find out what is known and not known about healthcare practices with a purposive sample. This study follows a scoping review in which we found that collaborative primary care models were recommended as the most feasible model for supporting family caregivers yet there was little literature on family physicians' perspectives on their roles in supporting family caregivers [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Much less is known about how primary care providers attend to the needs of family caregivers of older adults with chronic conditions that do not include cognitive impairment but that might require substantial family member time and effort to help such older adults remain as independent as possible at home. 5 Comorbidity burden is one source of heterogeneity in primary care for older adults, 5 and family members of patients with substantial comorbidity burden could be targeted for caregiver assessment if and when they accompany their relatives to primary care visits. Following the dementia care model, for other chronic or life-threatening conditions such as different types of cancer, congestive heart failure, and diabetes, the point of diagnosis would be an ideal springboard toward implementing caregiver assessment tools for those family members who accompany older adults to outpatient medical care visits.…”
mentioning
confidence: 99%